The impact of personality on timing and dynamics of partnership formation: A longitudinal approach a longitudinal approach - Okka Zimmermann (IU Internationale Hochschule, 2022)
In this study, I analyzed influences of the 'Big Five' personality traits onto transition risks into partnership and cohabitation and the likelihood of experiencing any of the different identified pattern of partnership dynamics (trajectories) within four years after the measurement of the Big Five. I used data of n = 6,748 respondents of the German PAIRFAM study. The Big Five personality traits were measured in a four-yearinterval in this representative study, with partnership events being prospectively recorded in all of the yearly panel waves. I used longitudinal methods (event history analysis, sequence analysis) to analyze influences on prospective partnership events and dynamics. I found that conscientiousness and extraversion were the main influences on partnership transitions and dynamics. Extraversion increased the likelihood of experiencing short or serial partnerships among men and women. Extraverted men also had a higher likelihood of transitioning into partnerships and experiencing fast processes of institutionalization. Conscientiousness decreased the likelihood of transitioning into a partnership and to experience short partnerships among women. Conscientiousness on the other hand positively influenced the likelihood of transitioning into cohabitation or serial partnerships among men. Contrary to expectations based on prior research, neuroticism played a minor role in predicting partnership transition risks and partnership trajectories. Only among men, neuroticism was positively associated with the risk of experiencing serial partnerships. I conclude that especially extraversion and conscientiousness influence the timing and sequencing of partnership events.
Keywords: 300; Personality; Personality Traits; Life Course; Event History Analysis; Sequence Analysis; Prospective Analysis; PAIRFAM